Analisis Kinerja Routing Protokol RIPng Dengan OSPFv3 Pada Jaringan IPV6 Tunneling: Harni Kusniyati, Raka Yusuf, Bayu Candra Wiraka - Jurnal, Redaksi Tim (PETIR, 2018)
The main objective of the development ipv6 is to meet need of ip addresses for a long term and improving the existing weaknesses in ipv4. But the transitional of the protokol version 4 to protokol version 6 cant be done by casually because due to the many infrastructure of the ipv4 network have been installed . For it is needed method to integrate ipv4 with ipv6 and one of the method is to use tunneling. The presence of tunneling network also needed routing protokol that support ipv6 protokol such as ripng and ospfv3 in ipv6 tunneling network. This paper is arranged to determine the performance of ripng dan ospfv3 routing protokols by analyzing the patch selection of data transmission, routing update analysis, speed time convergent analysis, analyzing by sending tcp data packet and sniffing analysis of data packet in tunneling network. The method used is literature study, computer simulation, and implementation on the test-bed. Data analysis showed that performance of ospfv3 is better than ripng because the speed of convergent time is faster. Ospfv3 need an average time as musch as 19 seconds but ripng need 178 seconds.on the test results of network throughput for tcp windows size that have 2, 4, 5, 6 kbyte capacity it take an average 121, 58 mbit/sec for ospfv3 and 117, 44 mbit/sec for ripng. For the overall performance of ripng and ospfv3 are not much different from its predecessor routing protokol in ipv4 network, it just for ripng and ospfv3 have support for 128-bit ipv6 addressing.